Serious Games and their use in Higher Education: An overview of projects created by the Serious Games Research Group at the University of Westminster (SG@W) - Economou, Daphne (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2024)
The keynote presentation elucidated the significant impact of serious games in Higher Education, clarifying terms like gamification, game-based education, and serious games. It provided a brief literature review, highlighting reasons for the growing recognition of serious games in supporting diverse pedagogical methods and styles, utilizing technology for active student engagement, and enhancing learning paradigms. Furthermore, the keynote discussed the formation of the Serious Games at Westminster Research group (SG@W), which bridges interdisciplinary research areas at the University of Westminster. SG@W aims to foster knowledge of effective game-based educational design across disciplines such as Computer Science, Engineering, Life Science, Liberal Arts, and Politics. This initiative has resulted in tailored educational resources, showcasing transformative pedagogical changes and significantly enriching student learning experiences beyond Computing. The group’s interdisciplinary approach enables a comprehensive understanding of pedagogical requirements across different domains, facilitating the provision of customized educational resources and technology.